Everyday Indigenous resurgence during COVID-19: a social media situation report. (December 2020) - Corntassel, Jeff; Edgar, Robynne; Monchalin, Renée; Newman, Carey
For Indigenous Nations on Turtle Island (Canada and the USA), the onset of COVID-19 has exacerbated food insecurity and adverse health outcomes. This situation report examines ways that Indigenous peoples on Turtle Island have met the challenges of the pandemic in their communities and their daily practices of community resurgence through social media. Drawing on the lived experiences of four Indigenous land-based practitioners, we found that social media can offer new forms of connection for Indigenous peoples relating to our foods, lands, waterways, languages, and our living histories.